THE DEGREE OF INJURY OF THE PAPYRACUTUS IN CLOSED BRAIN INJURIES (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
Today, in modern medicine, one of the diseases that causes high mortality and disability is closed brain injury. In general, against the background of damage to the central nervous system, secondary functional and morphological changes can develop in internal organs, including the pancreas. As a result of neuroendocrine and vegetative disorders, stress-hormonal effects, microcirculation in the body, increase the risk of pancreatic damage. Therefore, the study of the incidence of pancreatic pathology in BMYoJs is important in the field of medicine today.